Contribution of Body Height, Arm Muscle Strength, and Flexibility to Badminton Smash Performance among FIK UNM Makassar Students - Hasanuddin, M Imran (LITPAM, 2025)
Effective badminton smash performance depends on the integration of anthropometric characteristics, upper-limb strength, joint flexibility, and sport-specific stroke execution. This study examined the contribution of body height, arm muscle strength, and flexibility to badminton smash performance among students of the Faculty of Sport Science, Universitas Negeri Makassar. A quantitative descriptive-correlational design with regression analysis was used. The sample consisted of 40 students who had programmed badminton coursework, selected through simple random sampling as reported in the source document. Body height was measured using an anthropometric height test, arm muscle strength was assessed through a 20-second push-up test, flexibility was measured using a backward trunk-flexibility test, and smash performance was evaluated using a badminton smash skill test with 10 scoring opportunities. The data were analyzed using descriptive statistics, the Kolmogorov-Smirnov normality test, Pearson correlation, simple regression, and multiple regression. The results showed that body height, arm muscle strength, and flexibility were positively and significantly correlated with smash performance. In the multiple regression model, the three predictors jointly explained 69.8% of the variance in smash performance, with arm muscle strength emerging as the strongest predictor. However, flexibility was not a significant partial predictor after body height and arm muscle strength were entered into the model. These findings indicate that badminton smash performance is supported primarily by upper-limb strength, while body height and flexibility contribute as complementary physical factors. Training and talent-development programs should therefore integrate strength development, anthropometric consideration, flexibility training, and smash-specific technical practice.